The Triumph of Uncertainty Science and Self in the Postmodern Age - Tauber, Alfred I. (Central European University Press, 2022)
Tauber, a leading figure in history and philosophy of science, offers a unique autobiographical overview of how science as a discipline of thought has been characterized by philosophers and historians over the past century. He frames his account through science's - and his own personal - quest for explanatory certainty. During the 20th century, that goal was displaced by the probabilistic epistemologies required to characterize complex systems, whether in physics, biology, economics, or the social sciences. This "triumph of uncertainty" is the inevitable outcome of irreducible chance and indeterminate causality. And beyond these epistemological limits, the interpretative faculties of the individual scientist (what Michael Polanyi called the "personal" and the "tacit") invariably affects how data are understood. Whereas positivism had claimed radical objectivity, post-positivists have identified how a web of non-epistemic values and social forces profoundly influence the production of knowledge. Tauber presents a case study of these claims by showing how immunology has incorporated extra-curricular social elements in its theoretical development and how these in turn have influenced interpretive problems swirling around biological identity, individuality, and cognition. The correspondence between contemporary immunology and cultural notions of selfhood are strong and striking. Just as uncertainty haunts science, so too does it hover over current constructions of personal identity, self knowledge, and moral agency. Across the chasm of uncertainty, science and selfhood speak.